(untitled) (Prosiding Konseling Kearifan Nusantara (KKN), 2022)
Education in Indonesia is currently experiencing many changes. One of them is the emphasis on polite character education. This was done because it was considered that there was a decrease in the polite character of students with several influencing factors such as technological developments, the entry of foreign cultures, and the normal assumption of taboo things. To maintain and improve manners, the character education used is the local wisdom of the archipelago. This is because the local wisdom of the archipelago contains many values ​​of life order, one of which is courtesy. Politeness is a rule born in an environment that has been agreed upon and regulates how to behave. Manners are also one of the values ​​contained in Javanese customs that function as a regulator of orderly community life.